Energetic Electron Precipitation: Multievent Analysis of Its Spatial Extent During EMIC Wave Activity. Issue 4 (4th April 2019) - Capannolo, L.; Li, W.; Ma, Q.; Shen, X.‐C.; Zhang, X.‐J.; Redmon, R. J.; Rodriguez, J. V.; Engebretson, M. J.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; Spence, H. E.; et al.
Abstract: Electromagnetic ion cyclotron (EMIC) waves can drive precipitation of tens of keV protons and relativistic electrons, and are a potential candidate for causing radiation belt flux dropouts. In this study, we quantitatively analyze three cases of EMIC‐driven precipitation, which occurred near the dusk sector observed by multiple Low‐Earth‐Orbiting (LEO) Polar Operational Environmental Satellites/Meteorological Operational satellite programme (POES/MetOp) satellites. During EMIC wave activity, the proton precipitation occurred from few tens of keV up to hundreds of keV, while the electron precipitation was mainly at relativistic energies. We compare observations of electron precipitation with calculations using quasi‐linear theory. For all cases, we consider the effects of other magnetospheric waves observed simultaneously with EMIC waves, namely, plasmaspheric hiss and magnetosonic waves, and find that the electron precipitation at MeV energies was predominantly caused by EMIC‐driven pitch angle scattering. Interestingly, each precipitation event observed by a LEO satellite extended over a limited L shell region (Δ L 0.3 on average), suggesting that the pitch angle scattering caused by EMIC waves occurs only when favorable conditions are met, likely in a localized region. Furthermore, we take advantage of the LEO constellation to explore the occurrence of precipitation at different L shells and magnetic local time sectors, simultaneously with EMIC wave observations near the equator (detected by Van Allen Probes) or at the ground (measured by magnetometers). Our analysis shows that although EMIC waves drove precipitation only in a narrow Δ L, electron precipitation was triggered at various locations as identified by POES/MetOp over a rather broad region (up to 4.4 hr MLT and 1.4 L shells) with similar patterns between satellites. Key Points: We show three cases of proton and relativistic electron precipitation observed simultaneously with EMIC waves EMIC‐driven precipitation was observed by POES/MetOp satellites at different locations over a broad L‐MLT region Each precipitation event extended over Δ L 0.3 on average, showing that wave‐driven pitch angle scattering is localized